1986
DOI: 10.1002/jmor.1051900107
|View full text |Cite
|
Sign up to set email alerts
|

On the allometry of long bones in dogs (Canis familiaris)

Abstract: The allometric relations of diameter and length of humerus, ulna, femur, and tibia of 108 specimens, from 63 different breeds of dogs and 12 specimens of wolves, were calculated by means of model II of regression or major axis method. Only for the tibia were the values of wolves included in the cluster formed for dog breeds. Consequently, separate lines of regression were calculated for the other bones. Results agree in general with the exponents predicted by the theory of geometric similarity; however, the sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…When regressing long bone lengths and diameters to femur length in Canidae, Wayne (1986) found significant deviations from isometric scaling, which suggested low conformity with either GS or ES in the appendicular skeleton of canids. However, in a study with over sixty dog breeds, Casinos et al (1986) found that the scaling of humerus, radius and tibia conformed to GS but not that of the femur, which could explain the lack of conformity in Wayne’s study. Heinrich & Biknevicius (1998) showed that, in Martinae (Mustelidae), long bone dimensions tended to scale elastically, but conformity was also low.…”
Section: Introductionmentioning
confidence: 86%
“…When regressing long bone lengths and diameters to femur length in Canidae, Wayne (1986) found significant deviations from isometric scaling, which suggested low conformity with either GS or ES in the appendicular skeleton of canids. However, in a study with over sixty dog breeds, Casinos et al (1986) found that the scaling of humerus, radius and tibia conformed to GS but not that of the femur, which could explain the lack of conformity in Wayne’s study. Heinrich & Biknevicius (1998) showed that, in Martinae (Mustelidae), long bone dimensions tended to scale elastically, but conformity was also low.…”
Section: Introductionmentioning
confidence: 86%
“…Previous studies had reported scaling differences between femur and tibia (Casinos et al, 1986; Wayne, 1986; Bertram & Biewener, 1990; Raich & Casinos, 1991; Heinrich & Biknevicius, 1998; Christiansen, 1999a; Llorens et al, 2001; Lilje et al, 2003; Casinos et al, 2012). In those studies, the length of the tibia tended to scale slower than the length of the femur.…”
Section: Discussionmentioning
confidence: 95%
“…length and width dimensions scale in direct proportion to each other) or slightly negative allometric patterns (i.e. width dimensions increase at a lower rate than length dimensions) of skeletal growth in domestic dogs (Casinos et al 1986;Wayne, 1986). Analysis of adult specimens has shown similar patterns of geometric similarity in limb bone lengths and widths between domestic dogs and wild canids (Wayne, 1986).…”
Section: Specimensmentioning
confidence: 99%